(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Menstruation refers to the shedding of the uterine lining in the absence of fertilization, which occurs monthly in the female reproductive system. However, knowledge regarding menstruation is often inadequate, particularly among non-health students. This community service activity aimed to improve understanding of reproductive health through education. The study employed a one-group pre-posttest design with total sampling, involving 29 non-health female students from a university in Tasikmalaya. The pretest results showed an average score of 47.31, which significantly increased to 93.59 in the posttest. Participants with good knowledge increased from 2 to 29, while those with poor and moderate knowledge levels dropped to zero. Statistical analysis indicated a significant improvement after the educational intervention (p = 0.000). These findings demonstrate that reproductive health education effectively increases knowledge, particularly among non-health students. This initiative supports developing similar educational programs to enhance awareness and hygiene in reproductive health, ultimately improving public health quality.